Запровадження зарубіжного досвіду управління трудовим потенціалом у будівництві в Україні - Пащенко, Л. В. (Ways to Improve Construction Efficiency, 2012)
Foreign experience of labor potential management on the example of developed countries such as the U.S. and Japan is analyzed. Recommendations are given for adapting construction companies in Ukraine foreign management experience of labor potential.